2011
DOI: 10.1016/j.ajpath.2010.10.036
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Prostate Cancer Cell Rolling and Adhesion to Endothelium by 1α,25-Dihydroxyvitamin D3

Abstract: Adhesion of circulating prostate cancer (PCa) cells to the microvascular endothelium is a critical step during cancer metastasis. To study PCa cell rolling and adhesion behavior, we developed a dynamic flow-based microtube system to mimic the microvascular environment. We found that PCa cell rolling capacity is mediated by E-selectin and can be enhanced by stromal cell-derived factor-1 under different wall shear stresses. Using this device, we tested if the chemopreventive agent, vitamin D, could interfere wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 44 publications
3
41
0
Order By: Relevance
“…Loss of E-cadherin induces epithelial-mesenchymal cell transition via disruption of cell adhesion. Similar findings are reported in a study where increased levels of E-cadherin expression are accompanied with repressed cell rolling and reduced adhesion of the cancer cells to the endothelium (Hsu et al 2011).…”
Section: Introductionsupporting
confidence: 76%
“…Loss of E-cadherin induces epithelial-mesenchymal cell transition via disruption of cell adhesion. Similar findings are reported in a study where increased levels of E-cadherin expression are accompanied with repressed cell rolling and reduced adhesion of the cancer cells to the endothelium (Hsu et al 2011).…”
Section: Introductionsupporting
confidence: 76%
“…In this context, several in vitro studies have shown that the activity of CYP27B1 and its contribution to 1,25(OH) 2 D 3 production is lost in tumors with an aggressive phenotype (Fleet et al, 2012). On the other hand, Hsu et al (2011) reported that CYP27B1 was present in normal prostate epithelia cells (PECs). However, its enzyme activity was reduced in cells isolated from BPH while it was virtually absent in cells isolated from prostate cancer patients.…”
Section: Effects Of Malignant Transformation On 1-a-hydroxylase (Cyp2mentioning
confidence: 99%
“…Although a direct inhibiting effect of these enzymes in prostate cell growth inhibition appears unlikely, it is reasonable to hypothesize that they may indirectly mediate the chemopreventive effects of 1,25(OH) 2 D 3 by preventing DNA damage caused by ROS. Finally, recent finding by Hsu et al (2011) show that Vit D may indirectly affect tumor cell invasion and metastasis by facilitating prostate cancer cell aggregation through the increase of E-cadherin expression. However, Ajibade et al (2014) recently reported that prolonged treatments with calcitriol in homozygous male TRAMP mice resulted in the development of a resistant and more aggressive form of prostate cancer associated with increased distant organ metastasis.…”
Section: Effects Of Vitamin D On Prostate Cancer Cellsmentioning
confidence: 99%
“…Both proand anti-aggregation forces contribute to promoting cancer dissemination: loss of cohesion forces in the primary tumor allows individual cancer cells or small groups of cells to escape into the lymphatic and circulatory systems (2), whereas the increased cellcell adhesiveness of metastatic cells allows them to form multicellular homotypic aggregates, which have an increased chance of survival once detached from the primary tumor (3). Formation of these malignant cell aggregates also enhances their probability of interacting with endothelial cells in small capillaries and of their extravasation into surrounding tissues, which are necessary steps for metastasis (4,5).…”
Section: Introductionmentioning
confidence: 99%